(untitled) (Third Sector Social Economic Review, 2025)
This study aims to empirically examine the determinants of economic growth in Sub-Saharan African (SSA) countries. The study aims to contribute to the understanding of macroeconomic dynamics, which are of great importance for the sustainability of economic growth. In particular, four key elements frequently discussed in open economies—foreign direct investments, external debt stock, trade openness, and export variables—have been included in the analysis. The model, which was created for 21 SSA countries using annual panel data from 1975 to 2023, took into account both cross-sectional dependence and heterogeneity. In this regard, the estimates were made using the Dynamic Common Correlated Effects Mean Group (DCCEMG) method. According to the empirical findings, foreign direct investment has a positive and statistically significant effect on economic growth. On the other hand, it was found that the external debt stock has a negative and significant effect on economic growth. Trade deficit and export variables, on the other hand, did not show a statistically significant effect. Furthermore, the study investigated the causal relationship between the variables. Findings from the Emirmahmutoğlu–Köse causality test revealed no significant relationships at the panel level. It was observed that the causal relationship emerged more at the country level and in a heterogeneous manner. The findings of the study highlight the need to develop policy recommendations aimed at promoting structural reforms to encourage foreign direct investment, strengthening debt management, and transforming foreign trade into a değeri-added-oriented structure in order to achieve sustainable growth in SSA countries. In this context, the study contributes to the literature both in terms of its regional scope and methodological approach.